2019
DOI: 10.3390/nano9071028
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Self Nano-Emulsifying Drug Delivery System Loaded with Citraland Its Antiproliferative Effect on Colorectal Cells In Vitro

Abstract: Citral is an active compound naturally found in lemongrass, lemon, and lime. Although this pale-yellow liquid confers low water solubility, the compound has been reported to possess good therapeutic features including antiproliferative and anticancer modalities. The self nano-emulsifying drug delivery system (SNEDDS) is a type of liquid-lipid nanocarrier that is suitable for the loading of insolubilized oil-based compound such as Citral. This study reports the design and optimization of a SNEDDS formulation, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 42 publications
(66 reference statements)
0
21
0
Order By: Relevance
“…In fact, the negatively charged groups of hydroxyl and ester in the GMS molecules are the reasons for negative zeta potential of lipid coated CNPs 18 . The zeta potential value of more than ±30 mV confirms the sufficient stability of NPs 56,57 …”
Section: Resultsmentioning
confidence: 84%
“…In fact, the negatively charged groups of hydroxyl and ester in the GMS molecules are the reasons for negative zeta potential of lipid coated CNPs 18 . The zeta potential value of more than ±30 mV confirms the sufficient stability of NPs 56,57 …”
Section: Resultsmentioning
confidence: 84%
“…Also, based on the UV-Vis spectrometry analysis (not shown), it was deduced that 0.073 mmol of FITC moieties were covalently mounted per gram CNC which was more than the amount reported in previous literature [24,45]. In terms of surface charge, as presented in Table 1, it was found that conjugation of FITC had altered the zeta potential of CNC from −38.6 mV to −17.7 mV while the Ð improved from 0.703 to 0.371, which was considered acceptable for the delivery application [46].…”
Section: Resultsmentioning
confidence: 85%
“…Self-emulsifying drug delivery systems (SEDDs) ( Figure 9 ) have sparked profound interest from pharmaceutical researchers and industries through mainly antibiotic and antiviral SEDDs products in the market [ 186 ]; this micro/nanosystem offers droplet sizes of 5 µm to 200 nm [ 187 ] and <100 nm as well [ 188 ]. It can enhance the oral delivery of various therapeutic agents with different physicochemical properties [ 189 , 190 ], with either initial in vitro burst release, followed by a gradual-release phase or a sustained release profile [ 191 , 192 , 193 , 194 ]. SEDDs exist as liquid and solid formulations, where the solid form is suggested to provide better stability, reproducibility, and patient compliance, in addition to ease of process control, and various pharmaceutical dosage forms production (powders, capsules, tablets, or pellets) with the possibility of developing a controlled in vitro release attitude by mixing these dosage forms with suitable polymers or coating with polymeric films [ 193 , 195 ].…”
Section: Opportunities and Limitations Of Nanosystems For Mafld Thmentioning
confidence: 99%